The Kinta story - Govan H. W (Kuala Lumpur : Malayan Film Unit)
Documentary about Kinta in Malaya 1948
Photography, M. S. Lee, Md. Zain ; editor, Ronnie Tan
Narrator: Hugh Clancy, Geoff Raymond
Keywords: Kinta (Perak) -- History